An inconvenient text : is a green reading of the Bible possible? - Habel, Norman C. (ATF Press, 2009)
The Bible is an inconvenient text! There are numerous passages that are 'grey' rather than 'green'. These passages depict God or humans destroying or de-valuing parts of creation. What if we dare to read these 'grey' texts from the perspective of the victims--Earth and the domains of Earth? How then would we relate to these de-valued parts of creation? And, how does the Gospel contribute to resolving this dilemma?